(untitled) (Perner’s Contacts, 2014)
The article deals with issue of logistic audit. In current time this area isn’t regulated with any standard or norm. Logistic audit is focused on diagnosis of logistic processes of company which are specific for every sector of business. The contribution is focused on logistic audit in area of transport services.